Effect of Clostridium difficile toxin A on human intestinal epithelial cells: induction of interleukin 8 production and apoptosis after cell detachment. Issue 3 (March 1996) - Mahida, Y R; Makh, S; Hyde, S; Gray, T; Borriello, S P
Abstract : Clostridium difficile is the aetiological agent of pseudomembranous colitis, and animal studies suggest the essential role of secreted toxin A in inducing disease. This study examined the biological responses to toxin A by human intestinal epithelial cells. Confluent monolayers of Caco2, HT29, and T84 cells and primary epithelial cells in organ cultures of human colonic biopsy specimens and after detachment with EDTA were studied. Interleukin 8 was assayed using enzyme linked immunosorbent assay (ELISA). Purified C difficile toxin A induced cell rounding and detachment of monolayers of the epithelial cell lines. Cells in detached monolayers initially remained viable while adherent to each other. Subsequently, an increasing number of apoptotic cells appeared in suspension. Exposure to toxin A for 24 hours induced interleukin 8 production in T84 and HT29 cells. Toxin A also induced epithelial cell rounding, detachment, and apoptosis in organ cultures of human colonic biopsy specimens. During culture (in medium only), EDTA detached colonic epithelial cells produced interleukin 8 and cell death occurred by apoptosis. Colonic disease by C difficile may be initiated by toxin A mediated induction of epithelial cell interleukin 8 production and apoptosis after cell detachment from the basement membrane. Studies on isolated (toxin untreated) colonic epithelial cells suggest that interleukin 8 production and apoptosis occur as a consequence of cell injury and detachment.